Prevalence of Metabolic Syndrome and Its Prediction by Simple Adiposity Indices in Thai Adults - Hung Nguyen Ngoc; Wantanee Kriengsinyos; Nipa Rojroongwasinkul; Wichai Aekplakorn (Journal of Health Science and Medical Research (JHSMR), 2021)
Objective: Thai adults, have increased risk of being diagnosed with metabolic syndrome (MetS). Hence, early discrimination of MetS, with a simple and high accuracy index, appears necessary. However, the application of the discriminating ability of Lipid Accumulation Product (LAP), which is an emergent indicator of central lipid accumulation, to MetS among Thai people has not been investigated. This present study’s purposes were to investigate the nationwide prevalence of MetS, and the ability of LAP in discriminating this disorder. Material and Methods: Cross-sectional secondary data analysis was performed in 2018, using primary data from the Thai National Health Examination Survey, 2009. A total of 18,642 Thailanders ≥18 years were recruited. MetS was diagnosed by the National Cholesterol Education Program/Adult Treatment Panel III (NCEP/ATP) and International Diabetes Federation (IDF). Results: Overall, the prevalence of MetS-NCEP/ATP and MetS-IDF in Thai adults was 20.0% and 27.0%, respectively. LAP showed outstanding discriminating ability for MetS in both definitions (the cut-off point of 34.38 and 37.96 cm.mmol/L; area under the curve of 0.889 and 0.915 for NCEP/ATP and IDF, respectively). LAP performed the closest agreement in discriminating MetS-NCEP/ATP (κ=0.598, p-value<0.001) and MetS-IDF (κ=0.577, p-value<0.001). Logistic regression analysis exhibited a strong association of the LAP cut-off point with MetS, with the odds ratio being from 23.37 to 27.22 (p-value<0.001). Conclusion: These study results revealed that LAP was strongly associated with MetS, had an outstanding and reliable diagnostic accuracy for discriminating MetS in Thai adults, which might be helpful for early detection of MetS among vulnerable populations.